Compliment Strategies Used by The Judges in Indonesian and American Idol 2019: A Cross-Cultural Pragmatics Study - Muji Agustiyani (Script Journal: Journal of Linguistics and English Teaching, 2020)
Background: This is a contrastive study that compares the investigation on the patterns of compliments strategies used by the judges in Indonesian Idol and American Idol 2019. This study aims at describing the compliment strategies addressed by the judges in two reality talent shows, that’s a singing competition, and to reveal the differences of cultural values between the two societies. Methodology: The data is collected from the two YouTube accounts for the top three finalists’ performance by utilizing the observation method with the note-taking technique. Ye’s compliment strategies theory (1995) and Holmes’ syntactic patterns of compliments (1995) are employed in analyzing the data. Findings: The result showed a significant difference between Indonesian and American judges in the way they give compliments. Indonesian judges prefer to use more explicit compliments while American judges prefer implicit compliments instead. Conclusion: It then revealed the contrastive cultural reflection of western people that is supposed to be ‘more ‘direct’ in the way of speaking’ (Wierzbicka, 2003). On the other hand, the finding exhibited contrast results from conventional perception upon Indonesian cultural predilection to ‘indirectness’ in the way of speaking. Keywords: American Idol 2019; Compliment Strategies; Cross-cultural Pragmatics; Indonesian Idol 2019; The Judges.